Equating Business Value of Innovative Product Ideas - Brad, S. (Cranfield University Press, 2009)
Investing in new product development crucially depends on the capacity to estimate the business value of the product idea in the very early phases of the development process. Several empirical formulations have been proposed by now in this direction, but they lack of scientific tools to relate the business potential of the new product with the key decision-making factors. Strategic and general dimensional analyses are applied to define the relationship between the product business value and the influential factors. A key finding is the strong non-linear relationship between the business value of the new product and the market acceptance.
Organised by: Cranfield University
Keywords: New product business value; product innovation; dimensional analysis